Naimbag nga malem, Hilagang Luzon! evaluating the structure and credibility of regional television news programs in Northern Luzon - Francisco, Maureen M. 1993-; Peralta, Anna Francesca S. (2014)
"Regional news programs are an understudied component in the field of mass media. Hence, this study aims to bridge this research gap by evaluating two aspects: structure and credibility. In assessing the structure, the Multimodality theory is utilized to which interact in the narrative presentation of news. Credibility, divided into three dimensions: message, source, and overall news, is assessed by viewers from Baguio and La Trinidad. The predominant regional news programs in Northern Luzon ABS-CBN's TV Patrol Northern Luzon and GMA-7's Balitang Amianan were evaluated. Content analysis revealed that though they serve as the provider of local news, there are still underrepresented places that receive limited coverage within Northern Luzon. It was also revealed that these news programs mirror the theme of their national news program counterparts which were designed to communicate credibility. Viewers perceived these regional news programs to be moderately credible. However, these audiences were found to be peripheral viewers who have evaluated based on surface credibility, given their limited understanding of news. Guided by Hall's Encoding Decoding theory, thus study concludes that there is a disjunction between the encoded message and the decoded reading of news."